2020
DOI: 10.1111/aogs.14016
|View full text |Cite
|
Sign up to set email alerts
|

Normotensive preterm delivery and maternal cardiovascular risk factor trajectories across the life course: The HUNT Study, Norway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Although we did not find evidence for cardiovascular risk factors accounting for any of the excess cardiovascular risk in women with history of preterm birth, it is possible that this was due to insufficient statistical power or that the cardiovascular risk factors in our study were continuously measured while those of Tanz et al 22 were dichotomous. Our results are, however, consistent with our previous findings that life course trajectories of cardiovascular risk factors in women with a history of normotensive preterm birth do not differ from those of women with history of normotensive term birth 31 .…”
Section: Discussionsupporting
confidence: 92%
“…Although we did not find evidence for cardiovascular risk factors accounting for any of the excess cardiovascular risk in women with history of preterm birth, it is possible that this was due to insufficient statistical power or that the cardiovascular risk factors in our study were continuously measured while those of Tanz et al 22 were dichotomous. Our results are, however, consistent with our previous findings that life course trajectories of cardiovascular risk factors in women with a history of normotensive preterm birth do not differ from those of women with history of normotensive term birth 31 .…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, it is the first to investigate the role of genetic liability for CHD in APOs, conducted in a large, well-characterized, and genetically homogeneous population. This complements previous studies that have shown associations of cardiovascular risk factors (e.g., high blood pressure, dyslipidemia, impaired glucose tolerance) with APOs [ 2 7 ], by using a GRS that captures environmental (i.e., genetic risk of higher body mass, smoking, education) as well as likely biological risk for CHD. Unlike those previous studies, interpretation of the magnitude of one SD difference in a genetic risk score for CHD is unclear.…”
Section: Discussionsupporting
confidence: 53%
“…Adverse pregnancy outcomes (APO), such as miscarriage, stillbirth, hypertensive disorders of pregnancy (HDP), gestational diabetes (GD), small for gestational age (SGA), large for gestational age (LGA), and spontaneous preterm birth (sPTB), may unmask a woman’s underlying liability for cardiovascular disease, identifying women who “fail” the cardiometabolic stress test of pregnancy [ 1 ]. Preconception cardiovascular risk factors are associated with APOs [ 2 7 ] and the extent of physiological changes of pregnancy including vasodilation, decreases in glucose, and changes in lipoprotein subclasses and biomarkers of low-grade inflammation [ 8 ]. Moreover, adjustment for preconception cardiovascular risk factors attenuates the relationship between APOs and maternal post-partum risk of cardiovascular disease [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44] Similarly, much-though not all-of the risk of CVD associated with preeclampsia history is accounted for by the emergence of traditional cardiovascular risk factors, such as hypertension, after pregnancy. 34,45 Both the existence and variability in prepregnancy and postpregnancy cardiometabolic risk factors may suggest useful preeclampsia subtypes.…”
Section: Different Long-range Outcomes Of Preeclampsia As Indicators ...mentioning
confidence: 99%